1996
DOI: 10.1021/ja953092e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Heme Self-Assembly in Phospholipid Vesicles

Abstract: The use of weak, intermolecular forces to orchestrate the contruction of multicomponent systems in membranes has significant implications in diverse areas of chemistry, biology, and medicine. We describe here the construction and characterization of multi-heme molecular ensembles in phospholipid vesicles. A trianionic zinc porphyrin was designed to bind cytochrome c at the membrane surface, while being anchored to a membrane spanning manganese porphyrin in the membrane interior via a terminal imidazole. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…The possible reason is that the redox center of cyt c easily penetrated into the shorter chain length of lipids. The same tendency was observed in the previous work [32] studied for the electron transfer in vesicles composed of lipid bilayer. It showed that the electron transfer rate between the redox centers decreased as the chain length of lipids increased due to a low driving force at large distances.…”
Section: The Electron Transfer Rate Of Cyt C On the Lipid Layerssupporting
confidence: 89%
“…The possible reason is that the redox center of cyt c easily penetrated into the shorter chain length of lipids. The same tendency was observed in the previous work [32] studied for the electron transfer in vesicles composed of lipid bilayer. It showed that the electron transfer rate between the redox centers decreased as the chain length of lipids increased due to a low driving force at large distances.…”
Section: The Electron Transfer Rate Of Cyt C On the Lipid Layerssupporting
confidence: 89%
“…Uroporphyrin I with eight carboxylate groups caused formation of a ground‐state complex with cyt c leading to static fluorescence quenching of uroporphyrin I by cyt c 6. Groves and co‐workers constructed a sophisticated multiporphyrin assembly by partly using electrostatic interactions between an anionic zinc porphyrin and cyt c 7. In 1997, Hamilton and co‐workers reported a well‐designed protein receptor composed of a calix[4]arene building block and four peptide loops with eight carboxylate groups 8.…”
Section: Thermodynamic Parameters For Complexation Of Cyt C With Cdm‐mentioning
confidence: 99%
“…353 The construction and characterization of multi-heme ensembles in phospholipid vesicles have been described. 354 Aggregation of stilbene derivatized fatty acids and phospholipids in monolayers and vesicles has been studied. 355 A number of bis-cationic dimeric lipids have been synthesized and the vesicles formed show widely different membrane organizations with exceptional thermotropic properties.…”
Section: Hydrogenationmentioning
confidence: 99%